Maternal salivary testosterone in pregnancy and fetal neuromaturation. Issue 7 (9th September 2017) - Voegtline, Kristin M.; Costigan, Kathleen A.; DiPietro, Janet A.
Abstract: Testosterone exposure during pregnancy has been hypothesized as a mechanism for sex differences in brain and behavioral development observed in the postnatal period. The current study documents the natural history of maternal salivary testosterone from 18 weeks gestation of pregnancy to 6 months postpartum, and investigates associations with fetal heart rate, motor activity, and their integration. Findings indicate maternal salivary testosterone increases with advancing gestation though no differences by fetal sex were detected. High intra‐individual stability in prenatal testosterone levels extend into the postnatal period, particularly for pregnancies with male fetuses. With respect to fetal development, by 36 weeks gestation higher maternal prenatal salivary testosterone was significantly associated with faster fetal heart rate and less optimal somatic‐cardiac integration. Measurement of testosterone in saliva is a useful tool for repeated‐measures studies of hormonal concomitants of pregnancy. Moreover, higher maternal testosterone levels are associated with modest interference to fetal neurobehavioral development.